Адвокатська етика у науковій спадщині Є. В. Васьковського - Корнієнко, Ірина Валеріївна; Корниенко, Ирина Валерьевна; Kornienko, I. (My University, 2013)
Research of lawyer’s ethics in the writings of E. V. Vaskovskiy, a prominent representative of Odessa Law School, is analyzed. The author’s classification of legal matters on the criterion of morality, and specific ethical foundations of lawer’s activity revealed by E. V. Vaskovskiy is displayed.
Корнієнко І. В. Адвокатська етика у науковій спадщині Є. В. Васьковського / І. В. Корнаєнко // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 461-467.
Keywords: етика адвоката; одеська школа права; спадщина Є. В. Васьковського; класифікація юридичних справ за критерієм моральності; специфіка етичних основ діяльності правозахісників та судових представників; этика адвоката; одесская школа права; наследие Е. В. Веселовского; классификация юридических дел по критерию моральности; специфика этических основ деятельности правозащитников и судебных представителей; ethics lawyer; Odessa Law School; Heritage EV Veselovsky; classification of legal cases under the criterion of morality; the specificity of the ethical foundations of human rights defenders and judicial representatives